2019
DOI: 10.5858/arpa.2019-0375-ra
|View full text |Cite
|
Sign up to set email alerts
|

Primary Leiomyosarcoma of Bone: Review and Update

Abstract: Context.— Leiomyosarcoma of bone is a rare primary osseous sarcoma characterized by smooth muscle differentiation and absence of malignant osteoid formation. Leiomyosarcoma of bone is diagnostically challenging; this can be improved with greater awareness of this entity and the ability to differentiate it from its histologic mimics. Because of its rarity, only a small number of studies are available in the literature. These factors contribute to our limited understanding of its pathology, prognosis, and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 21 publications
(45 reference statements)
2
24
0
Order By: Relevance
“…This study found high‐grade tumors, initial distant metastases, nodal metastases, and tumor size ≥5 cm were each negative predictors of survival for both PLB and SLMS when grouped together. These results seem to align with the current literature detailing the aggressive nature of leiomyosarcoma, namely SLMS 5,15,16,18,19 . However, very few data describe the tumor characteristics of PLB, nor do they identify very many prognostic factors as these studies are mostly limited to case reports and small series 4,5,14,17,20–25 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study found high‐grade tumors, initial distant metastases, nodal metastases, and tumor size ≥5 cm were each negative predictors of survival for both PLB and SLMS when grouped together. These results seem to align with the current literature detailing the aggressive nature of leiomyosarcoma, namely SLMS 5,15,16,18,19 . However, very few data describe the tumor characteristics of PLB, nor do they identify very many prognostic factors as these studies are mostly limited to case reports and small series 4,5,14,17,20–25 .…”
Section: Discussionsupporting
confidence: 85%
“…Then in 1991, the immunohistochemical profile of PLB was further elucidated by Meyers et al, 3 who observed that PLB, which had often been misdiagnosed as malignant fibrous histiocytoma or fibrosarcoma, is a distinct clinicopathologic entity that may be more common than previously recognized. Since then, few studies have cited modern histopathological capabilities as a potential cause for an increased incidence of both PLB and SLMS 15 . Despite the reported increase in the incidence of these tumors over time, however, there is a lack of data informing the proper management of PLB, as well as SLMS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sinonasal tract LMSs are exceptionally rare with no more than 100 cases reported in the English literature [4]. LMS can also occur in bone, as primary or secondary tumor localization from distant sites, although the former is rare, with about 0.7% incidence of all primary malignant bone tumors [5].…”
Section: Introductionmentioning
confidence: 99%
“…No markers of myogenic tumors are observed in fibroblastic osteosarcoma lesions, distinguishing them from LMSB (7,27). And SATB2 is a relatively specific marker of osteosarcoma which is also helpful in differentiating between LMSB and osteosarcoma (7,27). Metastatic sarcomatoid carcinoma has a unique immunohistochemical feature as it expresses p63 and PAX8 and lacks the markers of myogenic tumors such as SMA and desmin.…”
Section: Discussionmentioning
confidence: 99%